2008
DOI: 10.2500/ajr.2008.22.3216
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Intraoperative Volume Computed Tomography Scanner for Endoscopic Sinonasal and Skull Base Procedures

Abstract: Intraoperative volume CT scanning was successfully performed in 25 patients undergoing ESS. Because additional surgical intervention was performed in 24% of cases, this technology may have an important role in endoscopic sinonasal and skull base procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…Recently, cone-beam CT systems (CBCT) with flatpanel detectors have been evaluated for sinus applications as an alternative to conventional multi-row detector CT (MDCT) [21]. However, low tissue contrast and inferior visualisation of thin anatomical structures prevent safe detection of inflammation in the examined region [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cone-beam CT systems (CBCT) with flatpanel detectors have been evaluated for sinus applications as an alternative to conventional multi-row detector CT (MDCT) [21]. However, low tissue contrast and inferior visualisation of thin anatomical structures prevent safe detection of inflammation in the examined region [22].…”
Section: Discussionmentioning
confidence: 99%
“…More recent clinical studies have also provided qualitative evidence that intraoperative CBCT provides high-quality definition of bony anatomy, which can lead to refinement of surgical strategy. 70,71 In a series of 25 patients undergoing ESS, Batra et al 71 found that residual bony partitions and stent locations could be visualized with intraoperative CBCT scans, leading to surgical revision. CBCT has also been used recently to evaluate contrast delivery during sinus irrigation after ESS.…”
Section: Sinus Imaging/frontal Recessmentioning
confidence: 99%
“…The xCAT intraoperative CBCT scanner (Xoran Technologies), a cousin of the MiniCat, has been evaluated in clinical scenarios at the skull base as well, with favorable preliminary results. 71,86 …”
Section: Skull Basementioning
confidence: 99%
“…[5][6][7] To date, there have been few studies comparing image quality in cone beam CT (CBCT) scans with that in multislice CT. 8 Cadaver and clinical studies have provided the principle evidence for the application of CBCT imaging to endoscopic sinus surgery, concluding that both spatial and soft-tissue contrast were sufficient to aid surgical navigation in the sinonasal cavity. [9][10][11] Preliminary evidence suggests that CBCT may be suited to specific imaging tasks in the context of bony structural evaluations enabling low-dose assessment of sinonasal anatomy.…”
Section: Introductionmentioning
confidence: 99%